Representing EEG source localization using Finite Element Method - Jatoi, M.A. (2013)
Finite Element Method (FEM) is a numerical tool usually used to solve various problems related to electromagnetic field, biomechanics, stress analysis etc. In this paper, the finite element is proposed as a solution to the localization problem of the active sources inside the brain. This localization is termed as the EEG Inverse problem. The solution to EEG inverse problem with less localization error, high resolution and less computational complexity leads to better understanding of human brain behavior and helps neurologist and neurosurgeons in curing various neurological disorders. The implementation of the FEM in solving EEG inverse problem is explained and then a pseudo code in MATLAB is designed and explained for the application to solve the problem. However, for illustration purpose, the solution to the 1D electromagnetic problem through FEM is plotted to elaborate graphically the procedure. Â© 2013 IEEE.